Cultural evolution accelerated human range expansion by more than two orders of magnitude - Charles Perreault (Proceedings of the National Academy of Sciences, 2026)
Humans occupy a geographic and ecological range wider than that of any other extant vertebrates, having rapidly expanded into nearly every habitat on the planet. This expansion was driven not only by biological adaptations but, crucially, by cultural evolution—a process that enabled the rapid and cumulative acquisition of adaptive behaviors and technologies. Here, I quantify the unique contribution of cultural evolution by comparing the global human range to mammalian ranges aggregated at various taxonomic ranks. I show that achieving the human range would require about 88 My of lineage divergence, over 2,200 species, and a nearly four-order-of-magnitude range in body mass. Yet, cultural evolution also allows humans to adapt at finer spatial scales, as evidenced by ethnolinguistic groups occupying smaller, more ecologically specialized territories than species. These findings highlight the unique role of cultural evolution in accelerating human ecological adaptation.